Entrepreneurial Leadership Impact on MSME Women’s Business Perfomance In Denpasar City - Made Putri Ariasih; Komang Endrawan Sumadi Putra; I Nengah Suarmanayasa (Jurnal Ekonomi, 2024)
This study investigates the impact of entrepreneurial leadership on the performance of women-owned Micro, Small, and Medium Enterprises (MSMEs) in Denpasar City. Focusing on 130 female entrepreneurs, the research utilizes partial least squares through SmartPLS 3. Findings reveal a positive and significant correlation between entrepreneurial leadership and business performance. Thus, a higher level of entrepreneurial leadership corresponds to enhanced business performance. These outcomes underscore the explanatory power of entrepreneurial leadership in influencing variations in MSMEs run by women in Denpasar City. The study recommends leadership training, emphasizing values like vision, human resource management, technology, and risk-taking, contributing to governmental initiatives. Moreover, it provides valuable insights for female-led MSMEs and the Denpasar City government to elevate business performance through effective entrepreneurial leadership.